Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
x/(two - x)^ two + one /(two - x) = zero
x divide by (2 minus x) squared plus 1 divide by (2 minus x) equally 0
x divide by (two minus x) to the power of two plus one divide by (two minus x) equally zero
x/(2 - x)2 + 1/(2 - x) = 0
x/2 - x2 + 1/2 - x = 0
x/(2 - x)² + 1/(2 - x) = 0
x/(2 - x) to the power of 2 + 1/(2 - x) = 0
x/2 - x^2 + 1/2 - x = 0
x divide by (2 - x)^2 + 1 divide by (2 - x) = 0
Similar expressions
x/(2 + x)^2 + 1/(2 - x) = 0
x/(2 - x)^2 + 1/(2 + x) = 0
x/(2 - x)^2 - 1/(2 - x) = 0
x/(2 - x)^2 + 1/(2 - x) = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]